Indonesian Marriage Legal System Construction In Order to Protect Children From Marriage Law That is Not Recorded - . Amnawaty (UBL, 2013)
The legal system of marriage in Indonesia there are three kinds. First Indigenous legal the system, theSecond the system of Islamic law, the three Western legal the system. Indigenous legal systems ofmarriage can still be found in the country of Indonesia both ritual of